Third-Age Learners and Approaches to Language Teaching - Jaroslav Kacetl; Blanka Klímová (MDPI AG, 2021)
Foreign language learning in the third age is one of the popular activities among the elderly. The question remains as to how to teach a foreign language to older adults properly. The first objective of this review was to identify suitable pedagogical approaches, teaching methods, or strategies for teaching foreign languages to third-age learners. The second objective was to determine whether foreign language learning later in life is beneficial. The authors used a method of literature review to achieve these goals. The former objective was not fully achieved as there is no clear outcome, although some generalizations based on other review studies can be made. Namely, foreign language teaching among the older generation should be student-centred and a communicative method should be implemented with a special focus on talking about familiar topics and listening comprehension to facilitate a senior's foreign language learning. In addition, the teaching methods ought to incorporate real life experiences and provide relevant content. Respect should also be paid to the fact that older adults have intrinsic rather than extrinsic motivation to learn a foreign language. The latter objective was attained since older people can benefit from learning a foreign language at a later age in many ways, including areas like travelling, social inclusiveness, improvement of cognitive skills, and overall well-being.